THE HISTORICAL ECONOMIC AND SOCIAL DIMENSION OF CORPORATE SOCIAL RESPONSIBILITY (THE CASE OF THE FURS SECTOR) - Mavridis, Dmitrios; Pouliopoulos, Leonidas; Pouliopoulos, Teophilas (Journal of European Economy, 2017)
Kastoria and Siatista two of the most historical regions of Western Mace¬donia with rich cultural, commercial and craft-based activity, are the only regions in Europe that managed to survive the whirlwind of globalisation and still maintain fur manufacturing alive even though significantly smaller. Based on the facts that we have available up to date, fur manufacture and trade in these regions are dated from the 15th century, and both activities have brought forth many achieved tradesmen with rich offer as benefactors and sponsors not only in their mother country, but also in their places of residence. Of course back then the term corporate social responsibility was unknown but the love for ones country, patriotism, benefaction, and any other act of social contribution and pure patriotism, were itself another form of expression, that resembled more that of «the so¬cial corporate responsibility» instead of the corporate social responsibility. These therefore, the economic, social and charitable acts of people from another time we will be discussing in order to prove that, the current activities of enterprises on environmental issues, social sensitivity, culture, training etc, did not emerge out of nowhere, but in reality pre-existed from the older years. They were simply presented and characterized differently, as different were the needs of each time. Beyond this however, we will also be referring on the necessity for the craft-based sector of fur manufacturing, to organise a network in order to both continue with the tradition of their predecessors and also further develop this value adding activity as much for the whole industry but also for the end-product itself.